68Ga DOTA-Exendin PET/CT for Detection of Insulinoma in a Patient With Persistent Hyperinsulinemic Hypoglycemia. (August 2018) - Parihar, Ashwin Singh; Vadi, Shelvin Kumar; Kumar, Rajender; Mittal, Bhagwant Rai; Singh, Harmandeep; Bal, Amanjit; Walia, Rama; Shukla, Jaya; Sinha, Saroj Kumar
Abstract : Abstract: Insulinomas are the most common functioning pancreatic neuroendocrine tumors and the leading cause of persistent hypoglycemia with hyperinsulinemia in adults. Glucagon-like-peptide-1 (GLP) receptor analogs are the latest agents being used in the detection of insulinomas, with initial reports suggesting high sensitivity due to universal GLP1 receptor expression on these tumors. PET/CT imaging in this patient using 68 Ga DOTA-Exendin, a GLP receptor analog, proved useful for accurate localization of the culprit lesion, aiding in the definitive management of the patient.